Pengaturan Hukum terhadap Pemanfaatan Tanah Kas Kalurahan di Kalurahan Condongcatur Kapanewon Depok Kabupaten Sleman - Diki Diki; Ika Kartika Sari (Pemuliaan Keadilan, 2025)
This study aims to examine the legal regulations related to the utilization of village land assets in the Condongcatur area, Sleman Regency. The approach used is an empirical juridical method with qualitative descriptive analysis. The legal materials analyzed include primary, secondary, and tertiary legal sources, with a focus on Law Number 6 of 2014 concerning Villages, Law Number 13 of 2012 concerning the Special Status of Yogyakarta, and Governor Regulation Number 24 of 2024. The results of the study indicate a discrepancy between legal provisions and implementation in the field, especially regarding the leasing and management of Village Treasury Land. This finding indicates the need for stricter supervision and increased transparency to the public.